2018
DOI: 10.12998/wjcc.v6.i14.745
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis in inflammatory bowel disease and other intestinal diseases

Abstract: For a long time, it was believed that apoptosis and necrosis were the main pathways for cell death, but a growing body of research has shown that there are other pathways. Among these, necroptosis, a regulatory caspase-independent, programmed cell death pathway, is supposed to be of importance in the pathogenesis of many diseases. The mechanism of regulating, inducing and blocking necroptosis is a complex process that involves expression and regulation of a series of molecules including receptor interacting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…19,20 This observation would suggest that apoptosis is a consequence of NEC rather than a cause of NEC, and raises the possibility that other pathways of cell death are involved. By contrast, necroptosis 21 is a highly inflammatory cell death pathway that has been linked to the pathogenesis of several diseases of mucosal inflammation, 22,23 including inflammatory bowel disease and allergic colitis in children, 24 and lethal ileitis during intestinal development. 25 Necroptosis is characterized by the activation of receptor-interacting protein kinases ([RIPK]1 and RIPK3), leading to the phosphorylation and plasma membrane translocation of mixed lineage kinase-like (MLKL) ( Figure 1A), 21 where it forms a pore complex allowing the massive release of proinflammatory damage-associated molecular patterns and the death of the cell.…”
mentioning
confidence: 99%
“…19,20 This observation would suggest that apoptosis is a consequence of NEC rather than a cause of NEC, and raises the possibility that other pathways of cell death are involved. By contrast, necroptosis 21 is a highly inflammatory cell death pathway that has been linked to the pathogenesis of several diseases of mucosal inflammation, 22,23 including inflammatory bowel disease and allergic colitis in children, 24 and lethal ileitis during intestinal development. 25 Necroptosis is characterized by the activation of receptor-interacting protein kinases ([RIPK]1 and RIPK3), leading to the phosphorylation and plasma membrane translocation of mixed lineage kinase-like (MLKL) ( Figure 1A), 21 where it forms a pore complex allowing the massive release of proinflammatory damage-associated molecular patterns and the death of the cell.…”
mentioning
confidence: 99%
“…Data from the present study identi ed that infection of macrophages with M. tuberculosis was associated with a lower level of FADD compared to M. bovis infection. FADD is an adapter protein to bind caspase 8 and caspase 10 precursors and is simultaneously activated and mediated cell signals with caspases 3, 6, and 7 to induce apoptosis [40]. This suggests that M. tuberculosis is able to inhibit signaling of caspases to execute the apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…25 The pro-inflammatory character of necroptosis plays a role in intestinal tissue damage, as represented by increased Paneth cell death and reduced goblet cells. 3 One study found that the expression of RIPK3 and MLKL might be an indicator of disease activity in patients with IBD. 6 Another study with similar findings in pediatric patients with IBD regarded necroptosis as an event that occurred when inflammation had been established.…”
Section: F I G U R Ementioning
confidence: 99%
“…1,2 Necroptosis has been associated with IBD because it may result in intestinal inflammatory damage, including increased Paneth cell death and reduced goblet cells. 3 Receptor-interacting protein kinase 3 (RIPK3), a key mediator of necroptosis, is elevated significantly in patients with IBD. 4,5 The elevation was also associated with increased disease activity.…”
Section: Introductionmentioning
confidence: 99%